Indigenous and scientific forecasts on climate change perceptions of arable farmers: Rwenzori region, western Uganda - Nkuba, Michael Robert; Chanda, Raban; Mmopelwa, Gagoitseope; Adedoyin, Akintayo; Mangheni, Margaret Najjingo; Lesolle, David; Kato, Edward (Springer, 2020)
Despite the dissemination of climate information from national meteorological systems, arable farmers still have challenges of dealing with climate-related risks. This study investigated the effect of using indigenous knowledge-based forecasts (IFs) and scientific knowledge-based forecasts (SFs) on the climate change perceptions of arable farmers in the Rwenzori region, Western Uganda. Data on socio-economic characteristics, use of forecasts, and climate change perceptions was collected from 580 arable farmers and the probit model was used in the analysis. The findings indicated that use of IFs only increased the likelihood of perceiving increase in the frequency in occurrences of droughts and floods. Using both SFs and IFs had a significant positive effect on perception of unpredictable rains and the increase in drought incidence among arable farmers. Although forecasts are important drivers of perceptions, other factors, such as gender, social capital, and dissemination of climate change information by radio, enhance climate change perceptions. Active participation of arable farmers in the dissemination of forecasts by national meteorological services could improve perceptions of climate related risks.